Impact of legislative changes on agricultural property trading - Blaszke, Małgorzata (Wpływ zmian ustawodawczych na obrót nieruchomościami rolnymi, 2020)
This paper attempts to describe selected elements regarding the situation on the agricultural property market and the assumptions of the policy in this respect in Poland. Particular attention was paid to legislative changes related to agricultural property trading. Statistical data from the Property Market Analysis and Monitoring System (AMRON), the Central Statistical Office, the Agency for Restructuring and Modernization of Agriculture (ARiMR) and the National Center for Agricultural Support, were used. The purpose of the study was to attempt to assess changes in land prices in Poland after systemic transformation. Attention was also paid to the issue of changes in the conditions for purchasing a property after the entry of the amended provisions of the Act on shaping the agricultural system came into force. An attempt was made to answer the question whether the introduced restrictions caused the prices of agricultural properties in Poland to change in spatial terms
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 5-19